CFD simulation and experimental measurement of nickel solids concentration distribution in a stirred tank - Synopsis - A. Ochieng (The Southern African Institute of Mining and Metallurgy, 2010)
Solids suspension influences the quality of mixing and energy requirement in a solid-liquid system, both of which determine the efficiency of industrial processes such as nickel precipitation. Nickel solids concentration distribution in a stirred tank was investigated using computational fluid dynamics (CFD) and experimental methods. The concentration distribution of the nickel solids was compared with that of sand and glass. The laser Doppler velocimetry (LDV) method was used to measure the velocity field for the liquid-only system and an optical technique was employed to determine the axial solids concentration distribution. Regions of in homogeneity in the tank were identified. It was found that, for a given solids loading, the solids concentration distribution depended on both particle size and particle size distribution. High solids loadings were investigated and a difference in the concentration distribution pattern was obtained with nickel, flint glass and sand particles. The CFD simulation results highlighted problems that could be associated with some conventional experimental methods of determining solids concentration distribution in a stirred tank. Keywords: nickel; CFD; simulation; mixing; solids suspension.